The Pauluskerk: an unorthodox church in Rotterdam - van der Hoeven, Frank (project baikal, 2014)
The tale of the rebuilding of the Pauluskerk (St. Paul’s Church) in the Dutch city of Rotterdam is a multilayered story that blurs the lines between architecture, societal issues, policymaking and urban redevelopment.The original Pauluskerk was built in the late 1950s in a city centre that was still recovering from the damage it suffered during the Second World War. The church may never have received the attention it has were it not for Reverend Visser, who developed the church into a refuge for the outcasts of Dutch society: asylum seekers, homeless people and drug addicts. Visser’s activism eventually evolved into the Perron Nul (Platform Zero) initiative, through which he organized support for the addicted and indigent on a scale not seen before in the city.The close proximity of the Pauluskerk to Rotterdam Central Station and the controversy surrounding its mission brought it slowly but steadily onto a collision course with the renewal and redevelopment of the station area, which would eventually lead to the demolition of the original Pauluskerk in 2007 and the construction of a new church building as part of the CalypSO project, designed by British architect William Alsop.This article brings these story lines together to showcase the complex process involved in an inner-city urban development founded in the well-established practice of local democracy, where consensus-seeking is the norm, even when this crosses societal borders.
Keywords: Сhurch; Pauluskerk; Rotterdam; CalypSO; Alsop; station development; Rotterdam Central Station; Visser; Perron Nul; homelessness; drug use